The relationship between management, audit committee and external auditor characteristics and modified audit opinions: evidence from Malaysian listed-firms - Raza, Ali (2021)
The study is motivated by the distinctive ownership structure in the Malaysian firms which differs from other developed markets. The role of corporate governance in such institutional settings is more crucial. This study primarily examines the characteristics of management, audit committee and the external auditor to ascertain how these governance mechanisms can enhance the financial reporting quality. The data is obtained from the annual reports of the companies listed in Bursa Malaysia. The data related to 120 firm-year observations which received modified audit opinions during the period 2012 to 2016 were matched with the firms which received clean audit opinions based on pre-determined criteria. In total 240 firm-year observations were included in the empirical examination. The statistical methods including univariate and multivariate regression models were employed to examine the study hypotheses. The findings reveal that CEO age, founder status and ownership have a strong association with modified audit opinion. Management is an integral part of the financial reporting process and the findings signify that powerful management considerably influences the reporting outcomes. The results related to the audit committee and its chair illustrate that number of meetings and the busyness of its chair are positively associated with the issuance of modified audit opinion. This finding is interesting in that a busy audit committee chair has a negative influence on the financial reporting quality of the firm. The external audit partner‟s busyness is also found to be positively associated with the modified audit opinion. This result shows that workload affects the audit efforts of external auditors. Further, interaction analysis reveals that there is a negative impact of the interaction between audit committee independence and CEO duality on the issuance of modified audit opinion. Overall, the results are significant in emerging markets context